Методы анализа данных и проблемы идентификации траекторий уединенных волн - Бомба, А.Я.; Турбал, Ю.В. (Проблемы управления и информатики, 2015)
Запропоновано методи ідентифікації траєкторій відокремлених хвиль за результатами дискретних спостережень в середовищі, де існує декілька хвиль одночасно. Методи складаються з окремих етапів аналізу швидкостей, пошуку взаємозв’язку даних та аналізу траєкторій. При побудові прогнозних траєкторій задача зводиться до перевірки сумісності систем моментних співвідношень, еквівалентній проблемі моментів Маркова. A method of solitary waves individual trajectories identification using the results of discrete observations is proposed. It is supposed an existance of a few solitary waves simultaneously. The method consists of several stages of velocity analysis, searching data relationship and trajectory analysis. A problem of building a predictive trajectories reduces to the verification of the compatibility of moment ratios systems which is equivalent to the Markov moment problem.